Inside installations : theory and practice in the care of complex artworks - Scholte, Tatja; Wharton, Glenn (Amsterdam : Amsterdam University Press, 2011)
Graham, Dan ; Dean, Tacita ; Plessi, Fabrizio ; Rosenbach, Ulrike ; Kosuth, Joseph ; Spinhoven, Bill ; Shaw, Jeffrey ; van Tijen, Tjebbe ; Viljus, Mart ; Kinoshita, Suchan ; Barrio, Artur ; Tuerlinckx, Joëlle ; Oppenheim, Dennis ; Sinclair, Ross ; Boltanski, Christian ; Burden, Chris ; Roth, Dieter ; Paik, Nam June ; Shonibare, Yinka ; Bogers, Peter ; Kehres, Rainer ; Hungerer, Sebastian ; Gabo, Naum ; Schoffer, Nicolas ; Tinguely, Jean ; Coleman, James ; Ruthenbeck, Reiner ; Beuys, Joseph ; Judd, Donald ; Andre, Carl ; Berkhemer, Madeleine
boek